2018
DOI: 10.1002/jcb.27101
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of endoplasmic reticulum disulfide oxidase 1α leads to trophoblast cell apoptosis through endoplasmic reticulum stress in preeclampsia

Abstract: Abnormal trophoblast cell apoptosis is implicated in the pathogenesis of pregnancy-related disorders including preeclampsia (PE), and endoplasmic reticulum (ER) stress has been considered as a novel pathway in the regulation of cell apoptosis. In this study, we observed that both apoptosis and ER stress are triggered in trophoblast cells under hypoxia as well as in the placenta of PE rats. Quantitative polymerase chain reaction and Western blot analysis showed that the expression of endoplasmic reticulum disul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…Hence, the miR-148/152 family may contribute to PE via modulation of DNA methylation patterns that leads to aberrant expression of downstream targets involved in metabolic and immune pathways (Figure 3). In agreement with the findings by Yang et al [42], a separate study in L-NAME-induced PE rats also reported a downregulation of DNMT1 in placentas and in hypoxia-treated trophoblasts [233]. In contrast, a study examining PE-like mice exposed to Bisphenol A (BPA) found a significant elevation in DNMT1 placental protein levels and an increase in DNMT1 expression in HTR-8/SVneo trophoblast cells exposed to BPA [234].…”
Section: Gene Targets Of Mir-148/152supporting
confidence: 81%
“…Hence, the miR-148/152 family may contribute to PE via modulation of DNA methylation patterns that leads to aberrant expression of downstream targets involved in metabolic and immune pathways (Figure 3). In agreement with the findings by Yang et al [42], a separate study in L-NAME-induced PE rats also reported a downregulation of DNMT1 in placentas and in hypoxia-treated trophoblasts [233]. In contrast, a study examining PE-like mice exposed to Bisphenol A (BPA) found a significant elevation in DNMT1 placental protein levels and an increase in DNMT1 expression in HTR-8/SVneo trophoblast cells exposed to BPA [234].…”
Section: Gene Targets Of Mir-148/152supporting
confidence: 81%
“…It has been found that increased Ero1α is involved in the development of ER stress-induced vascular endothelial dysfunction [20] and cardiomyopathy [21,22]. Upregulation of Ero1α exacerbates ER stress, and leads to cell death [23][24][25]. Ero1α is critical for ER stress-induced apoptosis of macrophages in insulin-resistant obese mice [26], and macrophage apoptosis occurs in advanced plaque induced by HHcy [12].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that DNA methylation occurs in all living creatures and plays an important role in many diseases. , Meanwhile, as the only family of proteases that can catalyze the process of DNA methylation, DNMTs also play an important role in gene expression regulation during pathological processes . Previous studies suggested that DNA methylation activated by DNMTs resulted in the silencing of gene expression, which induced cell apoptosis, inflammation, oxidative stress, etc., , while the inhibition of DNMTs could effectively alleviate these phenomena. There are a lot of studies on DNA methylation in AFB 1 toxicity and the development of hepatocellular carcinoma (HCC) .…”
Section: Introductionmentioning
confidence: 99%